Toward Post-Qualitative Research: Social Theatre on Maidan - Kostenko, N.; Tiahlo, K. (Социология: теория, методы, маркетинг, 2016)
The paper focuses on the problem of relevance of a post-qualitative approach in sociological research. The post-qualitative approach implies a freer format for data analysis and presen tation than it is required in qualitative stud ies. Actually, various types of case stud ies move to wards post-qual i ta tive in quiry in or der to save unique,vivid vi sual and ver bal ev i dence gath ered dur ing a so cial event and to make the obtained evidence useful for sociological knowledge. However, this problem needs further methodological discussion.